2016
DOI: 10.15406/moji.2016.03.00106
|View full text |Cite
|
Sign up to set email alerts
|

A New Biomarker in Patients with Vitiligo: A Case-Control Study

Abstract: Background: CRP is an acute phase protein secreted in the blood stream by the liver in response to inflammatory cytokines such as IL6 and several other systemic inflammation biomarkers. Since inflammatory and immune factors have a key role in the pathogenesis of vitiligo, we aimed to assess the relationship between the serum level of hsCRP (as a biomarker for systemic inflammation) and the pathogenesis of vitiligo. Methods:In this case-control study, we enrolled patients who had referred to the Dermatology Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In our study the mean serum hs-CRP in case group was higher 12.09 ± 11.64 than in control group 1.99 ± 2.05. Findings of our study was in concordance with the study by Reza Ghaderi 22 who found raised levels of hs-CRP in patients with generalized vitiligo. In our study the serum hs-CRP levels has statistically significant correlation with age of onset of disease indicating that early the age of onset of vitiligo, more will be the levels of hs-CRP while it has positive, statistically significant correlation with duration of disease indicating that longer the duration of disease more will be the levels of hs-CRP.…”
Section: Discussionsupporting
confidence: 93%
“…In our study the mean serum hs-CRP in case group was higher 12.09 ± 11.64 than in control group 1.99 ± 2.05. Findings of our study was in concordance with the study by Reza Ghaderi 22 who found raised levels of hs-CRP in patients with generalized vitiligo. In our study the serum hs-CRP levels has statistically significant correlation with age of onset of disease indicating that early the age of onset of vitiligo, more will be the levels of hs-CRP while it has positive, statistically significant correlation with duration of disease indicating that longer the duration of disease more will be the levels of hs-CRP.…”
Section: Discussionsupporting
confidence: 93%
“…Interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) mediate the modulation of the hepatic synthesis of acute-phase reactants, including CRP [15]. [18,19]. Our study also found that CRP levels were significantly higher in vitiligo patients compared to controls.…”
Section: Discussionmentioning
confidence: 50%
“…The studies consistently found that CRP levels were elevated in vitiligo patients compared to the control group [ 16 - 19 ]. Furthermore, Ghaderi et al and Solak et al reported that CRP levels were significantly higher in patients with generalized vitiligo compared to those with localized vitiligo [ 18 , 19 ]. Our study also found that CRP levels were significantly higher in vitiligo patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…This could be the possible evidence that curcumin and honey would have decreased his ongoing inflammation and oxidative stress. A case control study by Reza et al also showed that vitiligo patients have high hsCRP levels [ 29 ], as C-reactive protein is an acute phase reactant protein that is secreted in blood in response to inflammatory cytokines such as IL-6. A study by Shankar et al also reported high ESR levels in vitiligo patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%